A comparison study of the application of data assimilation in the short-term prediction of radiation and precipitation. (March 2018) - Ding, Huang; Cui, Fang; Wang, Zhijia; Zhou, Hai; Chen, Weidong
Abstract: Based on the meteorological observation of the DG plants in East China, the assimilation effect of the WRF in the summer of 2016 was studied. The results show that, in the case of using data assimilation, the model correctly predicted the occurrence time of precipitation, as well as the variation of the precipitation along with the time were well consistent with the observations, which gives more accurate downward shortwave radiation. The application of data assimilation techniques can provide reliable information to adapt to the high resolution of meso-scale meteorological model. Therefore, it provides the necessary technical support for the development of the distributed power generation.